The arms race between Greece and Turkey: Commenting on a major unresolved issue - Andreou, Andreas S.; Zombanakis, George A. (My University, 2006)
This paper focuses on the controversy that prevails concerning the extent to which an arms race is going on between Greece and Turkey. An examination of the recent contributions on this major issue beginning the year 2000 onwards suggests that the pronounced discrepancies among the conclusions drawn in these papers may be attributed to two major reasons among others: The effectiveness of the technique employed, as well as the inadequacy of certain policy recipes to treat actual defence incidents. Copyright © 2006 The Berkeley Electronic Press. All rights reserved.
Keywords: Relative military security; Arms race; Neural networks; Greece; Turkey